Hepatotoxicity associated with Garcinia cambogia: A case report - Yousaf, Muhammad Nadeem (World J Hepatol, 2019)
BACKGROUND: Herbal supplements (HS) for weight loss are perceived to be “safe” and “natural”, as advertised in ads, however, hepatotoxicity can be associated with consumption of some HS. Use of HS may be missed, as the patient may not report these unless specifically asked about these products, since they are often not thought of as medications with potential side effects or interaction potential. CASE SUMMARY: We reported a case of a 21-year-old female with morbid obesity who presented with abdominal pain for 1 wk associated with nausea, vomiting, anorexia and myalgias. She denied smoking tobacco, drinking alcohol, usage of illicit drugs, hormonal contraceptives, or energy drinks. There was no significant past medical or family illnesses. Her laboratory workup revealed acute liver failure. The workup for possible etiologies of acute liver failure was unremarkable. She was using a weight loss herbal supplement “Garcinia cambogia” for 4 wks. This case demonstrates the association of acute liver failure with Garcinia cambogia. CONCLUSION: Medical reconciliation of HS should be performed in patients with suspected acute liver failure and early discontinuation of HS can prevent further progression of drug induced hepatoxicity.